Dual-task interference as a function of varying motor and cognitive demands - McPhee, Anna Michelle; Cheung, Theodore C. K.; Schmuckler, Mark A. (Frontiers in Psychology, 2022)
Multi-tasking is a critical part of our daily lives. As such, understanding the processes by which actors are able to perform simultaneous behaviors, including both complex motor and cognitive tasks, is critical to understanding how it is individuals are able to perform in their everyday worlds. This study examined adults’ abilities to multi-task, or to engage in what has been called “dual-task behavior”, looking at the impact on both motor and cognitive performance to simultaneous variations in the difficulty of the motor and cognitive demands of the simple tasks of walking and counting. Generally, this study found that manipulations of motor difficulty (requiring participants to walk in either forwards or backwards directions) and cognitive difficulty (require participants to count by 2s or 3s, in either forwards or backwards directions) simultaneously influenced both motor and cognitive performance. For motor performance, dual-task demands appeared to most directly affect temporal and spatiotemporal parameters of gait. Interestingly, for cognitive performance, dual-task demands actually produced an increase in performance (relative to single task behavior). And finally, correlational analyses across participants observed that the dual-task performance was were correlated across motor and cognitive behavior, indicating that the impact of dual-task behavior as an individual difference parameter.